Fluid Dynamic Reactors: Large‐Scale Fast Fluid Dynamic Processes for the Syntheses of 2D Nanohybrids of Metal Nanoparticle‐Deposited Boron Nitride Nanosheet and Their Glycolysis of Poly(ethylene terephthalate) (Adv. Mater. Interfaces 16/2020). Issue 16 (20th August 2020) - Jeong, Jae‐Min; Jin, Se Bin; Park, Hong Jun; Park, Seung Hwa; Jeon, Hyeonyeol; Suh, Hoyoung; Park, Yong‐Ju; Seo, Donghyuk; Hwang, Sung Yeon; Kim, Do Hyun; Choi, Bong Gill
Abstract : The unique mass and heat transfer of fluidic‐flow control system provides advantages for organic and inorganic syntheses compared to the static reactors. In article number 2000599, Sung Yeon Hwang, Do Hyun Kim, Bong Gill Choi, and co‐workers demonstrate that the fluid dynamic reactor using Taylor‐Couette flow enables to high‐throughput process for exfoliation of hexagonal boron nitride and uniform deposition of metal nanoparticles onto the exfoliated boron nitride surface. Moreover, this fluid dynamic process significantly enhances catalyst‐based glycolysis reactions of poly(ethylene terephthalate).